Peran MUI Kota Palangka Raya terhadap Kebijakan Pemerintah dalam Pencegahan Penyebaran Covid-19 - Sanawiah Sanawiah (Anterior Jurnal, 2021)
Role of Indonesian Council of Ulama (MUI) Palangka Raya on Government Policy of Palangka Raya in preventing of spreading Corona Virus Maqasid Syari’ah perspective. To know the appeal of Palangka Raya MUI in controlling the spread of Covid-19. One of the Palangka Raya City Government policies was making instructions about the acceleration of handling Covid-19 in the Red Zone Area of Palangka Raya. All these policies did not reduce the number of positive patients and death. The increased spread of the Covid-19 case in Palangka Raya data source Media Center of task force Kalteng Covid-19 as of December 3rd, 2020 confirmed 1502 positive people, 180 positive people under treatment, 59 recovered 1248 people, and 72 people died. This research method is empirical, with a historical approach, a conceptual approach, and a prophetic approach. The result of the research is that the revitalization of the function of the mosque/prayer room is urgent for relaxation. In this regard, it is appealed to the congregation to continue to pay attention to health protocols. However, there are still mosques that do not want to follow government regulations and the appeal of the MUI of Palangka Raya. At the same time, religion has also regulated in the theory of maqasihd shari'ah in preventing the spread of the virus, including hifdzu nafs (protecting the soul) maintaining the soul, including personal safety, efforts from the outbreak of the coronavirus.